Association of historical housing discrimination and colon cancer treatment and outcomes in the United States. Issue 28 (1st October 2022) - Hussaini, S. M. Qasim; Fan, Qinjin; Yabroff, K. Robin Robin; Pollack, Craig Evan; Nogueira, Leticia M
Abstract : 69 Background: In the 1930s, the federally-sponsored Home Owners' Loan Corporation (HOLC) created maps that directed mortgage financing based largely on a neighborhood's racial composition. American neighborhoods were subdivided into four risk-based rankings (A – best neighborhood, B – still desirable, C – in decline, and D – hazardous and mapped in red) for mortgage approvals and denials. "Redlining" resulted in racial segregation and systemic disinvestment in communities targeted for marginalization. We investigated the association between historical housing discrimination and contemporary diagnosis, treatment, and survival outcomes in colon cancer – a leading cause of cancer deaths amenable to early detection and treatment. Methods: Individuals diagnosed with colon cancer from 2007-2017 were identified from the National Cancer Database. Individuals residing within known zip code tabulation areas (ZCTA) in 196 cities with ≥10% HOLC coverage were included. Residences were assigned a HOLC grade (A, B, C, or D) based on the majority HOLC area represented. Multivariable logistic regression models (adjusted for age and sex) were used to investigate the association of housing discrimination and late stage (stages III/IV) diagnosis, time to chemotherapy initiation, and non-guideline-concordant care (no chemotherapy, surgery, or < 12 lymph node dissection). Multivariable Cox proportional hazard models with age as time scale were used to investigate the association of housing discrimination and overall survival. Results: There were 98, 335 patients with new diagnoses of colon cancer with median age 68 years. Individuals residing in HOLC D were more likely to be non-Hispanic White (59%), have public insurance (46%), and income < 40, 000/year. Compared to people living in majority HOLC A ZCTAs, living in majority HOLC D had higher odds of a late-stage diagnosis, and living in majority HOLC B, C, or D had higher odds of non-guideline concordant colon cancer care with longer time to chemotherapy initiation. For people living in majority HOLC C and D, overall survival for all stages and late stage was worse when compared to HOLC A ZCTAs. Findings were consistent in sensitivity analysis. Conclusions: Historical housing discrimination is adversely associated with contemporary colon cancer care and outcomes. Findings underscore the importance of state-and federal-level practices on mortgage lending regulation and fair housing practices in determining equitable cancer risk, access to care, and outcomes.Housing and cancer outcomes. HOLC Rank Late Stage Diagnosis (OR, 95% CI) Time to Chemotherapy Initiation (HR, 95% CI) Non-Guideline Concordant Care (OR, 95% CI) Overall Survival (HR, 95% CI) A Ref Ref Ref Ref B 0.96 (0.9, 1.0) 1.2 (1.1, 1.2) 1.1 (1.0, 1.2) 1.1 (1.0, 1.1) C 0.99 (0.9, 1.1) 1.2 (1.1, 1.3) 1.2 (1.1, 1.3) 1.1 (1.1, 1.1) D 1.1 (1.0, 1.1) 1.3 (1.2, 1.4) 1.4 (1.3, 1.5) 1.1 (1.0, 1.1) *OR, Odds Ratio; HR, Hazard Ratio.